Clinical parameters and cardiovascular risk factors related to heart failure with preserved ejection fraction: a comparative analysis between HFA-PEFF and H2FPEF Scores. (3rd October 2022) - Lazzeroni, D; Marchini, C; Centorbi, C S; Moderato, L; Brambilla, L; Bini, M; Guazzi, E; Magnani, G; Aschieri, D; Piepoli, M; Nicolini, F; Coruzzi, P
Abstract: Background: Heart failure with preserved ejection fraction (HFpEF) diagnosis remains challenging, since several mechanisms (diastolic and systolic reserve abnormalities, chronotropic incompetence, ventricular or vascular stiffening, atrial dysfunction, pulmonary hypertension, impaired vasodilation, endothelial dysfunction, energetic abnormalities and autonomic dysfunction) play different roles in HFpEF development. European Society of Cardiology HF guidelines recently suggested a stepwise non-invasive diagnostic approach consisting of three steps: the first is clinical, the second includes echocardiographic and laboratory data (natriuretic peptides), named HFA-PEEF score, and finally, in case of inconclusive findings, diastolic stress echocardiography is recommended. On the other hand, in United States, another multiparametric score, named H2FPEF, has been proposed for HFpEF diagnosis, and including, in addition to echocardiographic parameters, also clinical data; thereby more applicable in the outpatient clinical arena. Purpose: Whether there is a clinical overlap between the two scores (HFA-PEEF and H2FPEF) as well as whether the addition of clinical data to the HFA-PEEF could improve its ability to identify different HFpEF phenotypes is still an open issue and these were the aims of our study. Methods: HFA-PEEF and H2FPEF scores were systematically applied on 1, 156 consecutive subjects with preserved ejection fraction who undergone cardiovascular evaluation at the Cardiovascular Prevention Center of Fondazione Don Gnocchi & University of Parma. All subjects underwent cardiovascular risk assessment followed by echocardiography and cardiopulmonary exercise testing; due to the outpatient (non-acute) setting of the evaluation, natriuretic peptides assay was not performed. Clinical data and cardiovascular risk factors data were compared between different groups of HFpEF risk. Results: According to H2FPEF score, low risk (<40%) of HFpEF was found in 659 (57%), moderate in 300 (26%) and high (>75%) in 197 (17%); according to HFA-PEEF score, 675 (58%) had 0 or 1 point, 253 (22%) had 2 points and 230 (20%) had 3 or 4 points (moderate-to-high risk). Patients with higher HFA-PEEF score were older (p<0.001), had higher prevalence of HTN (p<0.001), diabetes (p<0.001), obesity (p<0.001), sedentary lifestyle (p<0.001), AF (p<0.001) and CCS (p<0.001) (figure 1). More specifically, AF was associated to a 6.3-fold higher risk (p<0.001) of high (3–4) HFA-PEEF Score, age >75 years to a 4.6-fold higher risk, HTN to a 3.6-fold higher risk (p<0.001), CCS to a 3.3-fold higher risk (p<0.001), obesity to a 2.2-fold higher risk (p<0.001), diabetes to a 1.9-fold higher risk (p<0.001) and sedentary to a 1.7-fold higher risk (p=0.001). Conclusions: Although HFA-PEEF score does not include clinical data, patients with older age, atrial fibrillation, hypertension, hypertensive heart, diabetes, sedentary lifestyle and chronic coronary syndrome show a higher ESC risk of HFpEF. Funding Acknowledgement: Type of funding sources: None.